Utilization of Testimonials Menu as Submission Media Information on Buyer Satisfaction on the Website E-Commerce Raharja Internet Café - Henderi, Henderi; Zcull, Harph; Putri, Cheetah Savana (Aptisi Transactions On Technopreneurship (ATT), 2019)
Raharja Internet Cafe is a facility at Raharja College, which provides various needs for Raharja's private lecture activities. Raharja Internet Cafe is used to help lecture activities by facilitating students such as computers, printers and scanners. Also helps students to install or service iPad. However, sometimes the facilities available at Raharja Internet Cafe are still experiencing problems so students are less interested in visiting Raharja Internet Cafe. This study uses 2 (two) methods, namely the literature review method and questionnaire. As a result, to make it easier for sellers and buyers to know the quality of services provided by Raharja Internet Cafe to Pribadi Raharja, Raharja Internet Cafe's website is used by adding testimonials menus. In the testimonials menu, there are many testimonials that have been given by Raharja Internet Cafe users. And the results obtained from the research conducted are that Raharja Internet Cafe is very helpful in lecturing activities